VALUASI EKONOMI MANGROVE DI DESA KEBUN AYU, KABUPATEN LOMBOK BARAT - Siti Dian Rosadi; Nisyawati; Mufti Petala Patria (Jurnal Pro-Life, 2020)
Research has been conducted on the economic valuation of Mangrove ecosystems in Kebun Ayu Village, West Lombok Regency. This study aims to calculate and analyze the economic value of Mangrove ecosystems. The study was conducted by observation and interview methods. Direct Economic value (DUV) is obtained from the direct use of Mangroves with a value of Rp29.474.000,00/ year. Indirect Economic Value (IDV) of Rp1.161.136.240,00/years, obtained from the assessment of Mangrove ecosystem services. The Existence Value (EV) is obtained by using the CVM (Contingent Valuation Method) with a value of Rp3.150.000,00/ year. The value of the Option Value (OV) is obtained from the value of Mangrove biodiversity with a value of Rp3.150.000,00/ year. Total Economic Value (TEV) of Mangrove ecosystems in Kebun Ayu Village is Rp1.196.910.240,00/years. Keywords: Kebun Ayu, Mangrove, Lombok, Economic valuation